2013
DOI: 10.1155/2013/696835
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Composition and Antibacterial and Cytotoxic Activities ofAllium hirtifoliumBoiss

Abstract: Allium hirtifolium Boiss. known as Persian shallot, is a spice used as a traditional medicine in Iran and, Mediterranean region. In this study, the chemical composition of the hydromethanolic extract of this plant was analyzed using GC/MS. The result showed that 9-hexadecenoic acid, 11,14-eicosadienoic acid, and n-hexadecanoic acid are the main constituents. The antibacterial activity of the shallot extract was also examined by disk diffusion and microdilution broth assays. It was demonstrated that Persian sha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
39
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(44 citation statements)
references
References 45 publications
5
39
0
Order By: Relevance
“…Moreover, an earlier study showed that garlic and onion, which both belong to the Allium hirtifolium genus, exhibited signifi cant cytoprotective effects on normal cells [Shrivastava & Ganesh, 2010]. Ismail et al [2013] demonstrated that 1.50 mg/mL extract from Allium hirtifolium was safe for mammalian cells. Our results showed that some of the studied garlic extracts did not suppress normal cell proliferation.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, an earlier study showed that garlic and onion, which both belong to the Allium hirtifolium genus, exhibited signifi cant cytoprotective effects on normal cells [Shrivastava & Ganesh, 2010]. Ismail et al [2013] demonstrated that 1.50 mg/mL extract from Allium hirtifolium was safe for mammalian cells. Our results showed that some of the studied garlic extracts did not suppress normal cell proliferation.…”
Section: Discussionmentioning
confidence: 99%
“…The relatively higher antimicrobial activity of the aerial parts extract could be indicative for the presence of some phenolic compounds such as (+)-catechin, apigenin and caffeic acid. Although antimicrobial activities of some Allium species have already been reported (Hannan et al 2010;Najjaa et al 2011;Ismail et al 2013;Bakht et al 2014), little attention was paid to their antibiofilm potential (Nidadavolu et al 2012;Ceylan 2014). In the antibiofilm quantification assay, a concentration dependent decrease in biofilm formation was observed in the test microorganisms when treated with the ethanol extracts of A. orientale.…”
Section: Resultsmentioning
confidence: 99%
“…Many investigations have been performed on antimicrobial activities of Allium species, for example, the antimicrobial activity of A. ascalonicum [2,25] and A. hirtifolium [9,13,19,27]. However, there is no information about the anti-dermatophyte activity of A. hirtifolium aqueous extract.…”
Section: Discussionmentioning
confidence: 99%
“…Many authors have examined the antimicrobial [9,13,19,27], antioxidant [28], anti-parasitic activities [31,32] and immunomodulatory effects [10,14] of A. hirtifolium extracts or essential oil.…”
Section: Introductionmentioning
confidence: 99%